2021
DOI: 10.3897/zookeys.1020.57921
|View full text |Cite
|
Sign up to set email alerts
|

Annelids of the eastern Australian abyss collected by the 2017 RV ‘Investigator’ voyage

Abstract: In Australia, the deep-water (bathyal and abyssal) benthic invertebrate fauna is poorly known in comparison with that of shallow (subtidal and shelf) habitats. Benthic fauna from the deep eastern Australian margin was sampled systematically for the first time during 2017 RV ‘Investigator’ voyage ‘Sampling the Abyss’. Box core, Brenke sledge, and beam trawl samples were collected at one-degree intervals from Tasmania, 42°S, to southern Queensland, 24°S, from 900 to 4800 m depth. Annelids collected were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 264 publications
1
8
0
Order By: Relevance
“…In particular, species that live buried in the sediment or attached to rocks are often missed by dredges and beam trawls used by most recent general study programmes. This was clearly demonstrated by Gunton et al [104] who studied the polychaete fauna from depths off the east coast of Australia (1000-4000 m), and while ampharetids were very well represented, with over 300 specimens belonging to more than six species, 10 specimens and 2 species of pectinariids were also present and described (Petta investigatoris Zhang, Hutchings and Kupriyanova, 2019 and P. williamsonae Zhang, Hutchings and Kupriyanova, 2019), and far fewer specimens of Terebellidae s.l. were collected, representing four genera but all in poor condition.…”
Section: Distribution Of Terebelliforms With Depthsupporting
confidence: 53%
“…In particular, species that live buried in the sediment or attached to rocks are often missed by dredges and beam trawls used by most recent general study programmes. This was clearly demonstrated by Gunton et al [104] who studied the polychaete fauna from depths off the east coast of Australia (1000-4000 m), and while ampharetids were very well represented, with over 300 specimens belonging to more than six species, 10 specimens and 2 species of pectinariids were also present and described (Petta investigatoris Zhang, Hutchings and Kupriyanova, 2019 and P. williamsonae Zhang, Hutchings and Kupriyanova, 2019), and far fewer specimens of Terebellidae s.l. were collected, representing four genera but all in poor condition.…”
Section: Distribution Of Terebelliforms With Depthsupporting
confidence: 53%
“…Additionally, Amphinomidae specimens recently collected from the abyssal South Pacific (ca. 4000 m) as part of the RV ‘Investigator’ voyage ‘Sampling the Abyss’ were made available for examination (see also Gunton et al 2021 ). These specimens were examined as described above.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The enlarged branchiae of chaetiger 5 suggest close affiliation of CCZ specimens to Bathychloeia sibogae Horst, 1910 described from the Banda Sea, depth of 1100 m. Since its original description and subsequent re-description (Horst 1912), specimens assigned to B. sibogae or B. cf. sibogae have been reported from vastly different geographic and more importantly bathymetric areas such as the Tasman Sea and off Kenya (Kirkegaard 1995), Guinea Basin in SE Atlantic in depths of 5048-5144 m (Böggemann 2009) and South Pacific in depths of 2566 m and 4260 m (Gunton et al 2021). Further, Böggemann (2009) suggested that syntypes (BMNH1885.12.1.11) of Chloenopsis atlantica (McIntosh) from the NE Atlantic (Canary Islands, ca.…”
Section: Bathychloeia Cf Sibogae Horst 1910mentioning
confidence: 99%
“…In the terrestrial and limnic realms, South America, Africa and Asia are in need of further taxonomic surveys (Figure 4, but see papers in this Special Issue for more information). Our knowledge about habitats such as extreme environments [92] and the deep sea is also very limited (e.g., [117]).…”
Section: Gaps Of Knowledge and Future Perspectivesmentioning
confidence: 99%